Factors affecting academic performance of college students in China during COVID-19 pandemic: a cross-sectional analysis - Li, Changle; Kang, Lili; Miles, Toni P.; Khan, M. Mahmud (Frontiers in Psychology, 2023)
Introduction: Understanding the factors that affected academic performance of students during the COVID-19 pandemic will help design effective interventions for improving students' academic performance during emergency situations as well as during regular academic environment. This cross-sectional study aimed to identify the factors that explain academic performance of students in China during the pandemic. Methods: Data on college students from the 2020 China Family Panel Studies were used, and the final sample consisted of 728 students. Ordered probit regression models were estimated to explain students' relative performance in the semester when the in-person classes were suspended by using various student and household-related variables and characteristics. To compute missing values in selected variables, a multiple imputation technique was applied. Results: The odds of poor academic performance declined with higher Internet use for academic purposes, but Internet use for entertainment increased the probability of being in the poor academic performance. College students who spent more time studying on college work were less likely to have poor academic performance. Discussion: This study identified the factors (Internet use and study time) associated with academic performance among Chinese college students during the COVID-19 pandemic.These results can be used to design policies to improve educational outcomes and to address educational inequalities.